Transcript of Conversation with David Malpass and Masood Ahmed on the Way Forward - Malpass, David; Ahmed, Masood (World Bank, Washington, DC, 2022)
These remarks were delivered by the World Bank Group President David Malpass in conversation with Masood Ahmed, the President of the Center for Global Development on May 26, 2022. They both discussed on the following topis: (i) respond to the COVID crisis and now to the latest set of crises from Russia's invasion of Ukraine; (ii) the world moves away from the dependence on Russian energy, then new supplies will be vital; (iii) COVID Vaccination; (iv) fighting climate change; (v) global public goods; (vi) climate change action plan; (vii) climate financing; (viii) sustainable debt finance process; (ix) food security and infrastructure development; (x) possible global recession; (xi) education sector; (xii) human capital index; (xiii) the G7 communique; and (xiv) low-income households.